ANALISA KARAKTERISTIK AGREGAT BETON DAUR ULANG TERHADAP KUAT TEKAN BETON - Husnah Husnah; Herlien Dwiarti Setio; Ivan Sandi Darma; Patria Kusumaningrum (Racic : Rab Construction Research, 2025)
The use of recycled aggregates in concrete production is an environmentally friendly alternative to reduce construction waste and the exploitation of natural aggregates. This study aims to analyze the influence of the characteristics of recycled concrete aggregate (RCA) on the compressive strength of concrete. The research method involves using aggregates derived from laboratory concrete waste, which are crushed and sieved to pass through a 25 mm sieve. The physical characteristics of RCA were tested, including bulk density, sieve analysis, organic content of fine aggregates, silt content, moisture content, specific gravity, water absorption, and unhydrated cement grain (UCG) analysis. Concrete specimens were prepared with 25%, 50%, 75%, and 100% RCA as a replacement for coarse aggregates, and their compressive strength was evaluated at the ages of 7, 14, and 28 days. The results showed that higher proportions of RCA in the concrete mix can lead to an increase in compressive strength.